PENGEMBANGAN MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) BERBASIS KOMUNITAS BELAJAR UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SD - Afies Rudit Setyono; Sitti Hartinah; Suriswo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the development and implementation of the Strengthening the Profile of Pancasila Students (P5) module based on a learning community, aimed at enhancing the pedagogical competencies of teachers in public elementary. The research is structured around three primary questions: (1) What are the needs analysis results for the P5 project module based on a learning community? (2) How is the design for implementing the P5 project module structured? and (3) What is the process of developing the P5 project module to improve the pedagogical competencies of teachers? A limited trial was conducted involving 20 teachers from the Ki Hajar Dewantara cluster, employing qualitative and quantitative methodologies. The findings reveal that the module's structure is coherent and user-friendly, effectively integrating local wisdom through narratives about Ki Gede Sebayu and Ki Ageng Anggawana. Teachers generally responded positively to the module's content, recognizing its relevance to Pancasila values, though they suggested the inclusion of more diverse and interactive activities to foster student engagement. Observational data indicated that students exhibited increased participation in project-based learning initiatives, although some teachers noted difficulties in maintaining students' focus during activities. The overall evaluation indicated that the module is effective in supporting teacher competency development, with an average score of 81.71% for the module's structure and 82.8% for the content, categorizing them as "Very Good."